Potensi Pengembangan Pantai Nyanyi sebagai Daya Tarik Wisata di Kecamatan Kediri, Kabupaten Tabanan, Bali. - Ni Putu Sri Utami Putri; Ni Ketut Sutrisnawati; I.B. Gde Upadana; Fatrisia Yulianie (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2022)
Pantai Nyanyi is a beach located in Tabanan Regency, Bali. This beach has a variety of tourism potential, both physical and non-physical potential. The existence of these various potentials can be developed as a tourist attraction. The purpose of this study is to describe the potential and analyze the weaknesses, opportunities and threats found on Pantai Nyanyi Tabanan so that the right strategy for developing a tourist attraction can be determined. This research uses descriptive qualitative analysis techniques. Primary data was obtained through direct observation to the research location and interviews with relevant sources, while secondary data was obtained by conducting a literature study using several journals that were relevant to the topic. The data is then analyzed using the SWOT Matrix method. The results of the study revealed that Pantai Nyanyi has tourism potential, both physical and non-physical potential. Its physical potential is in the form of beautiful and beautiful beach views and is still natural. Around the beach, there are hills and rock cliffs as well as a coastal forest. Pantai Nyanyi has waves that are big enough so it is suitable for surfing. Pantai Nyanyi is also a beautiful beach to relax while watching the sunset, this beach has a beautiful panorama to take pictures. Meanwhile, non-physical potential can be found in community activities as fishermen. Lack of promotion can be overcome by taking advantage of technological advances. promotion by the internet and social media. Another effort is to educate local people to be aware of tourism and the importance of maintaining the cleanliness and sustainability of the Pantai Nyanyi ecosystem.